2000
DOI: 10.1007/s004209900112
|View full text |Cite
|
Sign up to set email alerts
|

Indoor exposure to polycyclic aromatic hydrocarbons and carbon monoxide in traditional houses in Burundi

Abstract: It appears that the substantially high concentrations of the studied contaminants constitute a potential health hazard to the rural population of Burundi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
42
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(51 citation statements)
references
References 36 publications
8
42
1
Order By: Relevance
“…Pregnant women in this study had higher levels of creatinine adjusted OH-PAHs compared to levels observed in charcoal workers in Brazil (Kato et al, 2004), but are comparable to those observed in non-smoking women in a city in the industrial Ruhr Valley in Germany (Gündel et al, 1996). Concentration of creatinine adjusted 1-PYR was higher in female cooks who worked in a mill in China and cooked with wood, coal briquette or LPG (~2 times higher) (Chen et al, 2007), and in a rural Burundi population exposed to indoor biomass smoke mainly from the combustion of wood (~3.5 times higher) (Viau et al, 2000) compared to the pregnant women in this study. Concentrations of creatinine adjusted two-to four ring OH-PAHs (same as measured in this study) were also higher in women participating in woodstove intervention programs in the Santiago de Chuco Province in Peru: approximately 1.5 to 5 times higher before, and 1.1 to 3.5 times higher after the installation of improved woodstoves .…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…Pregnant women in this study had higher levels of creatinine adjusted OH-PAHs compared to levels observed in charcoal workers in Brazil (Kato et al, 2004), but are comparable to those observed in non-smoking women in a city in the industrial Ruhr Valley in Germany (Gündel et al, 1996). Concentration of creatinine adjusted 1-PYR was higher in female cooks who worked in a mill in China and cooked with wood, coal briquette or LPG (~2 times higher) (Chen et al, 2007), and in a rural Burundi population exposed to indoor biomass smoke mainly from the combustion of wood (~3.5 times higher) (Viau et al, 2000) compared to the pregnant women in this study. Concentrations of creatinine adjusted two-to four ring OH-PAHs (same as measured in this study) were also higher in women participating in woodstove intervention programs in the Santiago de Chuco Province in Peru: approximately 1.5 to 5 times higher before, and 1.1 to 3.5 times higher after the installation of improved woodstoves .…”
Section: Discussionmentioning
confidence: 68%
“…A few studies have characterized the risk of exposure to PAHs due to residential combustion of different biomass fuels by measuring PAH levels at breathing zone height in cooking environments (Bhargava et al, 2004;Hamada et al, 1991;Oanh and Dungs, 1999;Pandit et al, 2001) and under experimental conditions (Oanh et al, 2002) and report that various PAHs are elevated during the combustion of wood, kerosene, cow dung and coal briquette. Results of biomarker studies have shown that people exposed to smoke from biomass combustion have elevated levels of hydroxy-substituted PAHs in urine (Cavanagh et al, 2007;Kato et al, 2004;Li et al, 2011;Riojas-Rodriguez et al, 2011;Viau et al, 2000), and receive a significant PAH exposure from biomass smoke RiojasRodriguez et al, 2011). Reductions in urinary two-to four-ring OH-PAHs after the installation of improved woodstoves ranged from 19% to 52% in women participating in woodstove intervention programs in the Santiago de Chuco Province in Peru , and from 20% to 42% in women participating in a similar program in the state of Michoacan in Mexico (Riojas-Rodriguez et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The exposure concentration of BaP used in this study is within the range (10μg-2mg/ m 3 ) present in the environment from sources such as: aluminum smelter and coke oven battery industries (WHO, 1998); ambient air of highly polluted industrial cities (Chorazy et al, 1994); cooking oil and wood combustion fumes (Viau et al, 2000); home heating with coal-gas (WHO, 1998). Furthermore, the exposure concentration of BaP used in this study is close to the legally enforceable limit of 100μg/m 3 established for PAHs by the Occupational Safety and Health Administration (OSHA, 1998).…”
Section: Discussionmentioning
confidence: 99%